Availability of Sugar-Sweetened Beverages at Home as The Dominant Factor Related to Its Consumption Among Students of SMAN (State High School) 47 Jakarta, Indonesia, in 2022 - Nadhira Winindya Sari; Kusharisupeni Djokosujono; Diah Mulyawati Utari; Neni Rohayati (Indonesian Journal of Public Health Nutrition, 2022)
AbstractSugar-sweetened beverages (SSBs) are drinks added with simple sugar, which can increase the energy because of calorie-dense and high in sugar, but low in other nutrients. Excessive consumption of SSBs can cause nutritional problems, such as increasing the risk of overweight and obesity. This study aims to determine the relationship between SSBs consumption and various factor and the dominant factor of SSBs consumption among students of SMAN (State High School) 47 Jakarta in 2022. The cross-sectional study was conducted from November 2021 to June 2022 with 120 respondents. Primary data was taken using questionnaires and analyzed by univariate, bivariate (chi-square test), and multivariate (multiple logistic regression). Univariate analysis shows that 90% of respondents consumed high levels of SSBs. Bivariate analysis shows that pocket money, advertising and media exposure, and availability of SSBs at home have a significant relationship with SSBs consumption. Multivariate analysis shows that the dominant factor associated with SSBs consumption was the availability of SSBs at home. The school is advised to provide education about the impact of high SSBs consumption, provide mineral water refills, and encourage parents to provide healthy drinks at home. The government is advised to use social media for intervention, limiting unhealthy drinks ads, and implementing a policy of SSBs excise tax.Keywords: Sugar-sweetened beverages, adolescents, high school studentsAbstrakSugar-sweetened beverages (SSBs) merupakan minuman yang diberi tambahan gula sederhana yang menambah kandungan energi karena padat kalori dan tinggi gula, namun memiliki sedikit kandungan zat gizi lain sehingga dapat meningkatkan risiko kejadian gizi lebih. Penelitian ini bertujuan untuk mengetahui hubungan konsumsi SSBs dengan berbagai faktor dan mengetahui faktor dominan konsumsi SSBs pada siswa SMAN 47 Jakarta tahun 2022. Penelitian ini menggunakan desain studi cross sectional pada bulan November 2021 - Juni 2022 dengan jumlah responden sebanyak 120 orang. Data yang diambil adalah data primer dengan pengisian kuesioner. Data yang diperoleh selanjutnya akan dianalisis secara univariat, bivariat (uji chi-square), dan multivariat (uji regresi logistik ganda). Hasil analisis univariat menunjukkan 90% responden mengonsumsi SSBs tingkat tinggi. Hasil bivariat menunjukkan bahwa uang saku, paparan iklan dan media, serta ketersediaan SSBs di rumah memiliki hubungan yang signifikan terhadap konsumsi SSBs. Analisis multivariat menunjukkan bahwa faktor dominan yang berhubungan dengan konsumsi SSBs adalah ketersediaan SSBs di rumah. Pihak sekolah disarankan untuk memberikan edukasi gizi terkait dampak konsumsi SSBs berlebih, menyediakan tempat pengisian ulang air mineral, dan mengimbau orang tua siswa untuk menyediakan makanan sehat di rumah. Pemerintah disarankan untuk memanfaatkan media sosial sebagai media intervensi, membatasi iklan minuman yang kurang sehat, dan menerapkan kebijakan pengenaan cukai SSBs.Kata kunci: Sugar-sweetened beverages, remaja, siswa SMA